Pengaruh Model Pembelajaran Problem Based Learning Terhadap Hasil Belajar Matematika Kelas V SDN 3 Bangkleyan Blora - Khusnul Estining Tyas; Aries Tika Damayani; Intan Rahmawati (STKIP Andi Matappa Pangkep, 2022)
The purpose of this study is to determine whether there is an effect of the Problem Based Learning model on the learning outcomes of class V grade mathematics at SD Negeri 3 Bangkleyan Blora. This study used a quantitative approach with a quasi-experimental research design. Data collection techniques in this research are observation, interviews, tests and documentation. Based on the results of the data processing carried out, the value of the T test was obtained the sig value was 0,000 and the calculated t value was 4,318. The value of sig ˂ 0,05 or 0,000 ˂ 0,05. The value of t arithmetic ˃ t table or 4,318 ˃ 2,010. Based on the t test, H0 is rejected and Ha is accepted, it can be concluded that there is a significant influence between the Problem Based Learning model on mathematics learning outcomes.